Increase of Fungal Pathogenicity and Role of Plant Glutamine in Nitrogen-Induced Susceptibility (NIS) To Rice Blast - Huang, Huichuan; Nguyen Thi Thu, Thuy; He, Xiahong; Gravot, Antoine; Bernillon, Stéphane; Ballini, Elsa; Morel, Jean-Benoit (Frontiers in Plant Science, 2017)
Understanding why nitrogen fertilization increase the impact of many plant diseases is of major importance. The interaction between Magnaporthe oryzae and rice was used as a model for analyzing the molecular mechanisms underlying Nitrogen-Induced Susceptibility (NIS). We show that our experimental system in which nitrogen supply strongly affects rice blast susceptibility only slightly affects plant growth. In order to get insights into the mechanisms of NIS, we conducted a dual RNA-seq experiment on rice infected tissues under two nitrogen fertilization regimes. On the one hand, we show that enhanced susceptibility was visible despite an over-induction of defense gene expression by infection under high nitrogen regime. On the other hand, the fungus expressed to high levels effectors and pathogenicity-related genes in plants under high nitrogen regime. We propose that in plants supplied with elevated nitrogen fertilization, the observed enhanced induction of plant defense is over-passed by an increase in the expression of the fungal pathogenicity program, thus leading to enhanced susceptibility. Moreover, some rice genes implicated in nitrogen recycling were highly induced during NIS. We further demonstrate that the OsGS1-2 glutamine synthetase gene enhances plant resistance to M. oryzae and abolishes NIS and pinpoint glutamine as a potential key nutrient during NIS.